Effect of Slope Gradient on Soil Physiochemical Fertility Indices across Two Distinct Depth Layers in Horticultural Farm at Ibeku Opi-Agu, Nsukka, Nigeria - C. B. Okebalama; A. C. Onah; C. E. Awaogu (Journal of Applied Sciences and Environmental Management)
Topography is a critical determinant of the spatial distribution of soil properties, including nutrient retention and availability. The objective of the study was to assess the effect of slope gradient on soil physiochemical fertility indices across two distinct depth layers (0-20 cm and 20-40 cm) in a horticultural farm at Ibeku Opi-Agu in the Nsukka Local Government Area of Enugu State, Nigeria. The slope gradient at the crest, middle, and bottom was 8%, 5%, and 2%, respectively. The study employed appropriate standard procedures. The soil textures were loam, sandy loam and sandy clay loam across the slope gradients and soil depths. Slope gradients and soil depths and their interactions significantly (p ≤ 0.05) affected the proportions of the > 2.00, 0.50-1.00, 0.25-0.50 and <0.25 mm water stable aggregates, percent aggregate stability and saturated hydraulic conductivity of the soils, while bulk density, total porosity and particle size distribution of the soils were not affected. Saturated hydraulic conductivity decreased with decreasing slope gradient (crest > middle > bottom). The concentrations of soil organic carbon, and exchangeable sodium and potassium cations were significantly higher at the crest compared to the middle and bottom slope gradients. The results for the other soil chemical properties were statistically similar across slope gradients, soil depths and their interactions. We conclude that the topographic influence of an 8% slope gradient on soil properties is dependent on slope position. However, changes in soil fertility with depth are limited to physical properties, and not chemical properties of the soils studied.